A Three-Step Synthesis of 1,7-Diazaperylene and Derivatives - Langhals, Heinz; Reichherzer, Susanne; Mayer, Peter; Polborn, Kurt (Synthesis, 2020)
1,7-Diazaperylene and various derivatives were synthesised in an upscaleable route from 1,5-diaminoanthraquinone and its Meerwein reaction with acrylonitrile and subsequent cyclisation with ammonia. The application of tert-butyl alcohol as the solvent led to a significant improvement in the Meerwein reaction.
Keywords: heterocycles; perylene; aromatics; functional materials; UV/Vis spectroscopy